On extremum problems for Orlicz spaces of functions analytic in the unit circle - Terpigoreva, V. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. М. Терпигорева. Об экстремальных задачах для классов Орлича аналитических функций в единичном кругеV. Terpigoreva. Ekstremaliniai uždaviniai analizinių vienetiniame skritulyje funkcijų Orličo klasėse